Welcome, Brown Bird - Ray, Mary Lyn.; Sylvada, Peter (Orlando [Fla.] : Harcourt, 2004)
While a boy in North America urges his father not to cut down the trees where the wood thrush lives, a boy in South America awaits the return of the bird that he calls "la flauta" for its flute-like song.
Ages 3-7.
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection.
Keywords: Wood thrush -- Fiction; Birds -- Migration -- Fiction; Wood thrush -- Juvenile fiction; Birds -- Migration -- Juvenile fiction